INVESTIGATION CHARACTERISTICS OF PULP FIBERS AS GREEN POTENTIAL POLYMER REINFORCING AGENTS - Nanang Masruchin; Subyakto Subyakto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
INVESTIGATION CHARACTERISTICS OF PULP FIBERS AS GREEN POTENTIAL POLYMER REINFORCING AGENTS. Three kinds of pulp fiber (i.e. kenaf, pineapple and coconut fiber)were characterized as reinforcing agents in compositematerials to be applied at automotive interior industry.Abetter understanding on characteristics of fiber will lead to enhance interface adhesion between fiber and matrices. Furthermore, it will improve the properties of polymer significantly. Chemical, surface compositions as well as morphology of pulp fiber were investigated using TAPPI standard test method, Fourier Transform Infrared Spectroscopy (FT-IR) and optical microscopy, respectively. Further observation on morphology of the fiber was conducted by Scanning Electron Microscope (SEM). From this study, pineapple pulps showed the highest α-cellulose content than that of kenaf or coconut pulps. However, it has the lowest hemicellulose content among them. This condition takes responsibility for the difficulties of pineapple pulps defibrillation process.Much fines or external fibrillations are presence on both kenaf and pineapple pulp’s morphology, but it is not presence in the coconut pulps.Moreover, coconut fiber is shorter than the other two fibers with diameter size estimated in the order pineapple < kenaf < coconut pulps. FT-IR analysis shown quite similar absorption fromall pulps, except for coconut pulps due to the remaining lignin on the surface of fiber that showed by the presence of C-O phenol stretching at 1280 cm-1. Finally, it is reported that kenaf pulps fiber is suitable candidate for polymer reinforcing agents compared to pineapple and coconut pulps fiber.